Success Factors in Microfinance Greenfielding - Jansson, Tor (World Bank, Washington, DC, 2012)
The creation of new microfinance institutions (greenfielding) is a key International Finance Corporation (IFC) intervention to increase access to finance in countries where there are few institutions serving micro and small businesses. IFC uses this approach extensively in Africa and in post conflict countries, and has supported the creation of 12 microfinance banks in Sub-Saharan Africa over the past four years. Another five are in the pipeline. Before 2006, IFC had made a grand total of only four microfinance investments in the region ever. So this program represents an extraordinary expansion of IFC's microfinance activities in the region. The program's focus on greenfielding has enabled the Africa microfinance team to identify some key success factors that can be applied to future projects in Africa and elsewhere.